(untitled) (Architecture Image Studies, 2025)
Immaturity, as a state of behaviors, is a subject that negatively affects social relationships and the individual’s life. It is a subject that has been studied in scientific literature as a defense mechanism. It is wondered whether immaturity is related to digital technologies. This study aimed to develop a valid and reliable dimensional immaturity scale and examine its psychometric properties with social media analysis. For this purpose, data was collected from 320 people across Turkey on a voluntary basis. As a result of the studies carried out in the research, the 4-dimensional and 18-item Uskudar Immaturity Scale (USIMS) was developed. The dimensions of the scale are named as: (1) Hastiness, impatience and suggestibility, (2) Center of attention, (3) Impulsivity, (4) Tendency to stand out and emotional instability. The scale explained 57.57% of the total variance. The Cronbach Alpha value of the scale was found to be .87. In the confirmatory factor analysis study, the scale structure was confirmed. Some of the first results are: (a) The immaturity level of those who use social media for 4 hours or more a day was found to be the highest, (b) the immaturity level increases as the frequency of live chatting on social media increases, (c) they become happy when they receive likes on social media, (d) the immaturity level of those who stated that they had a relationship and ended their relationship by fighting on social media is observed. It was concluded that the developed scale needed to be applied to different samples in further studies.